Comparison between High Performance Liquid Chromatography and Capillary Electrophoresis in detecting Haemoglobin Constant Spring / Muhammad Ikmal Mohd Nizar ... [et al.] - Mohamed, Emida; Mohd Nizar, Muhammad Ikmal; Raja Sabudin, Raja Zahratul Azma; Camalxaman, Siti Nazrina; Sham Rambely, Azlin; Haron, Norhisham (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Two popular methods - High Performance Liquid Chromatography (HPLC) and Capillary Electrophoresis (CE) have been compared for diagnosis of Haemoglobin Constant Spring (HbCS). The performance of the methods was evaluated in terms of sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV). A total of thirty-two results were collected at HUKM which consisted of results derived from HPLC, CE and ARMS-PCR from December 2012 until December 2017. Results obtained showed CE demonstrated higher sensitivity, specificity, PPV and NPV compared to HPLC in the detection of HbCS.